Investigating the Impact of Digital Learning Ecosystem Activities on Enhancing Pre-service Teachers' Mathematical Literacy - Chananil, Supannika; Julakarn, Phuntipa; Promsatien, Yupawadee (International Journal of STEM Education for Sustainability, 2025)
This study examined the influence of Digital Learning Ecosystem (DLE) activities on the mathematical literacy of pre-service teachers, emphasizing the connection between theoretical knowledge and practical application. A cohort of 30 pre-service mathematics educators was chosen via simple random sampling. The study utilized a quasi-experimental design using pretest-posttests to evaluate the efficacy of DLE activities. The tools comprised four lesson plans grounded in DLE principles, a mathematical literacy exam consistent with the OECD's PISA methodology, and a satisfaction survey to assess participants' engagement and perceptions. The results demonstrated a statistically significant enhancement (p 0.001) in participants' mathematical literacy, accompanied by a large effect size (Cohen's d = 1.34), underscoring the considerable influence of DLE interventions. Participants indicated elevated satisfaction across multiple dimensions, including engagement (M = 4.70, SD = 0.42), perceived effectiveness (M = 4.63, SD = 0.48), and accessibility (M = 4.55, SD = 0.51). Qualitative feedback emphasized the significance of interactive components, including simulations, collaborative tools, and real-world problem-solving activities, in improving comprehension and motivation. These findings highlight the transformative capacity of DLE activities in pre-service teacher education, especially in enhancing critical thinking, problem-solving abilities, and mathematical literacy. The study provides important insights into the integration of digital tools into teacher training programs to prepare educators for increasingly digital classrooms. Future research should look at the long-term impacts and adaptability of DLE activities in different educational settings in order to improve their efficacy.